This strange eventful history : a philosophy of meaning : pairs of thinkers in philosophy, religion, science and art - Bradley, Paul (Algora Pub., 2011)
Meaning may appear elusive in our present divided world but a sense of meaning is essential for peace of mind. This book sets out to survey our options concisely, in the realms of philosophy, religion, science and art. Each chapter draws on the words of two (or more) prominent inter-related thinkers to help us form an opinion, often provocatively, with no holds barred! It steers a path towards an attitude of Cosmic Compassionate Plurality. All of us must seek at a personal and a general level for a philosophy of meaning in life, "this strange eventful history," to borrow a descriptiv.